Measurement-Based Analysis of 5G Cellular Network Interference on Radar Altimeters and Joint Power-Angle Control Mitigation Strategy - Zahra Rostamikafaki; Francois Chan; Claude D'Amours (IEEE Access)
The global deployment of 5G technology, particularly in the C-band (3.4-4.2 GHz), has introduced critical interference challenges for safety-critical avionics, such as radar altimeters (RAs), which are essential for safe aircraft navigation. This study investigates the impact of 5G base stations (BS) on RAs through airborne measurements conducted using a helicopter above and around a 5G BS. Signal strength and interference patterns were captured at various altitudes and distances, illustrating how out-of-band (OOB) and spurious emissions from 5G signals can interfere with RA readings. An optimization model was developed to minimize interference through joint power and angle control at the BS, balancing the trade-off between 5G signal quality and aviation safety. The proposed method significantly reduces interference while maintaining a minimum quality of service (QoS) for 5G users. Simulation results demonstrate that, compared to power-only control, joint control improves signal quality by approximately 15 dB while reducing interference, suggesting a viable solution for harmonizing 5G and aviation requirements. This work offers a novel approach to mitigating 5G interference on RAs and provides valuable insights for improving the coexistence of these critical systems.